On the upper and lower functions for the stable stochastic process - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Калинаускайте, О верхних и нижних функциях для устойчивых случайных процессов. IN. Kalinauskaitė, Atsitiktinių stabilių procesų viršutinių ir apatinių funkcijų klausimu. I